Sensors for mechatronics - Regtien, P. P. L. (Amsterdam ; New York : Elsevier, 2012)
Mechatronics is a multidisciplinary field combining Mechanical, Electronic, Computer, and other Engineering fields to develop intelligent processes and products. Based on thirty years of extensive work in industry and teaching, this book provides an overview of the sensors and sensor systems required and applied in mechatronics with an emphasis on understanding the physical principles and possible configurations of sensors rather than simply a discussion of particular types of sensors. Well illustrated with examples of commercially available sensors and of recent and future developments, this.
Front Cover; Sensors for Mechatronics; Copyright Page; Contents; Preface; 1 Introduction; 1.1 Sensors in Mechatronics; 1.1.1 Definitions; 1.1.2 Sensor Development; 1.1.3 Sensor Nomenclature; 1.1.4 Sensors and Information; Binary Sensors; Analogue Sensors; Image Sensors; Optical Imaging; Acoustic Imaging; Tactile Imaging; 1.2 Selection of Sensors; References to Cited Literature; Literature for Further Reading; Introductory Books on Sensors and Mechatronics; Books on Semiconductor Sensors; 2 Sensor Fundamentals; 2.1 Physical Quantities; 2.1.1 Classification of Quantities. 2.1.2 Relations Between Quantities2.2 Sensor Classifications; 2.2.1 Classification Based on Measurand and Application Field; 2.2.2 Classification Based on Port Models; 2.2.3 Classification Based on Conversion Principles; 2.2.4 Classification According to Energy Domain; References to Cited Literature; Literature for Further Reading; Some books and articles on quantities and systems; 3 Uncertainty Aspects; 3.1 Sensor Specification; 3.1.1 Sensitivity; 3.1.2 Non-linearity and Hysteresis; 3.1.3 Resolution; 3.1.4 Accuracy; 3.1.5 Offset and Zero Drift; 3.1.6 Noise; 3.1.7 Response Time. 3.1.8 Frequency Response and Bandwidth3.1.9 Operating Conditions; 3.2 Sensor Error Reduction Techniques; 3.2.1 Compensation; 3.2.2 Feedback Methods; 3.2.3 Filtering; Filtering Prior to Transduction; Filtering after Transduction; 3.2.4 Modulation; Multiplier as Modulator; Switch Modulator; Measurement Bridge as Modulator; 3.2.5 Demodulation; 3.2.6 Correction Methods; References and Literature; References to Cited Literature; Literature for Further Reading; Many Books on Instrumentation and Measurement Comprise Chapters on Accuracy and Noise Reduction, for Instance; 4 Resistive Sensors. 4.1 Resistivity and Resistance4.2 Potentiometric Sensors; 4.2.1 Construction and General Properties; 4.2.2 Electrical Characteristics; 4.2.3 Interfacing; 4.2.4 Contact-Free Potentiometers; 4.2.5 Applications of Potentiometers; 4.3 Strain Gauges; 4.3.1 Construction and Properties; 4.3.2 Interfacing; 4.3.3 Applications of Strain Gauges; 4.4 Piezoresistive Sensors; 4.4.1 Piezoresistivity; Piezoresistive Silicon Sensors; Piezoresistive Elastomers; 4.4.2 Micromachined Piezoresistive Sensors; Pressure and Force Sensors; Piezoresistive Accelerometers; 4.4.3 Applications of Piezoresistive Sensors. Tactile Sensors4.5 Magnetoresistive Sensors; 4.5.1 Magnetoresistivity; 4.5.2 Applications of Magnetoresistive Sensors; 4.6 Thermoresistive Sensors; 4.6.1 Thermoresistivity; 4.6.2 Resistance Thermometer; 4.6.3 Thermistors; 4.7 Optoresistive Sensors; References and Literature; References to Cited Literature; Literature for Further Reading; Books and Reviews on Magnetoresistive Sensors and Applications; Books and Review Articles on Tactile Sensors; 5 Capacitive Sensors; 5.1 Capacitance and Permittivity; 5.2 Basic Configurations of Capacitive Sensors; 5.2.1 Flat-Plate Capacitive Sensors.
Includes bibliographical references.
Keywords: Mechatronics; Microelectromechanical systems